Evaluation of the remainder term for the Thiele interpolation continued fraction - Pahirya, M. M.; Пагіря, М. М. (Institute of Mathematics, NAS of Ukraine, 2008)
We present an estimate of the remainder term for the Thiele interpolation continued fraction.